Improving rice sustainability through digital tools - Barnard, Jennifer; Vu Hong Trang; Nelson, Katherine (International Rice Research Institute, 2022)
To provide a platform for dialogue among the stakeholders on the challenges of reaching Vietnamese smallholder farmers with digital tools, the International Rice Research Institute (IRRI) organized a webinar titled ‘Improving Rice Sustainability through Digital Tools’. Part of the Agro-ecological transformation for inclusive and sustainable agriculture and food systems (TRANSITIONS) project, funded by the European Union through its DeSIRA initiative and managed by the International Fund for Agricultural Development (IFAD), the webinar identified the opportunities for improving access and use of digital tools and tailoring the services to meet the needs of farmers through inclusive co-production of digital tools.